Two isomeric metal–organic frameworks bearing stilbene moieties for highly volatile iodine uptake. Issue 14 (14th June 2022) - Tang, Jianping; Zhou, Shenghua; Huang, Mengyi; Liang, Zhenxin; Su, Shaodong; Wen, Yuehong; Zhu, Qi-Long; Wu, Xintao
Abstract : Two isomeric MOFs bearing stilbene moieties, which serve as promising candidates for highly volatile iodine uptake at room temperature, were prepared by adjusting the diffusion temperature. Abstract : Efficient, green, and economical removal of radioactive iodine (I2 ) has drawn worldwide attention for the safe development of nuclear energy. Metal–organic frameworks (MOFs) have been demonstrated to be potential candidates for I2 capture. Herein we report the synthesis of two novel isomeric MOFs bearing stilbene moieties for exceptionally high I2 adsorption. [Cd(hsb-2)(tsbdc)]·0.5DMF (HSB-W8 ) and Cd(hsb-2)(tsbdc) (HSB-W9 ), which exhibit two-dimensional and twofold interpenetrated three-dimensional structures, respectively, have been assembled from hydrogenated Schiff base ligands, hsb-2 (1, 2-bis(4′-pyridylmethylamino)-ethane) and trans-stilbene-4, 4-dicarboxylate (tsbdc), and Cd(NO3 )2 by the diffusion method. Such isomers arise from the different conformations of hsb-2 ligands controlled by diffusion temperatures. The π-electron-rich stilbene moieties render these Cd-MOFs ideal platforms for I2 capture. The adsorption capacities of HSB-W8 and HSB-W9 in I2 vapor at room temperature can reach up to 2.32 and 1.92 g g −1, respectively, which are comparable to the best-performing MOF materials reported so far. Furthermore, pseudo-second-order (PSO) kinetic model analysis, Fourier transform infrared (FT-IR) spectroscopy, Raman spectral analysis, density functional theory (DFT) calculations, and control experiments were performed to shed light on host–guest interactions and the iodine adsorption mechanism. This work develops a rational strategy to design and synthesise functional MOF materials for iodine adsorption.